Ethical challenges in primary care: a focus group study with general practitioners, nurses and informal caregivers. (21st June 2018) - Gágyor, Ildikó; Heßling, Arndt; Heim, Susanne; Frewer, Andreas; Nauck, Friedemann; Himmel, Wolfgang
Abstract: Background: General practitioners (GPs), nurses and informal caregivers are often jointly involved in healthcare situations in which ethical issues play an important role. Objectives: To describe ethical problems from the perspective of these three groups and to investigate whether there is a common experience of ethical issues in primary care. Methods: We conducted six focus groups with general practitioners, nurses and informal caregivers in Germany. We asked the participants to describe at least one experience of ethical problem in detail and documented the findings by an illustration software that visualized and structured the discussion. We used thematic analysis to identify ethical problems and to develop categories of ethical issues. Results: Problems reported barely overlapped. GPs had to do mainly with uncertainty about the scope and limits of their responsibility for patients. Nurses were concerned about bureaucratic and other barriers to professional care and about dual loyalty if they had to consider the conflicting interests of patients and family members. They often felt powerless and unable to act according to their professional standards. Informal caregivers reported problems that resulted from role strain and being both a family member and a caregiver. GPs, nurses and informal caregivers sometimes perceived the other parties as a source of ethical problems. Conclusions: All parties may benefit from ethics support services, a rarity in German primary care so far. Furthermore, nurses' self-confidence towards GPs, demanding patients and family members has to be strengthened. Informal caregivers, the most vulnerable group, need more attendance and tailored support.